Heat flow data of RV METEOR cruise M183 - Kaul, Norbert (PANGAEA, 2024)
Heat flow data, sampled during M183 within the RIFLOR project. Locations are along the Mid Atlantic ridge between 57° 29'N and 58° 18'N, mainly within the denominated Squid Pond. We used the 6 m Bremen heat probe with 21 channels. In-situ temperatures and thermal conductivities were derived using MHFRED, according to the inversion method of Villinger and Davis (2007).